Agrochemical Mixtures and Amphibians: The Combined Effects of Pesticides and Fertilizer on Stress, Acetylcholinesterase Activity, and Bioaccumulation in a Terrestrial Environment. (24th March 2019) - Van Meter, Robin J.; Adelizzi, Rose; Glinski, Donna A.; Henderson, W. Matthew
Abstract: Tank mixtures are popular within the agricultural community because they are time‐ and cost‐effective, but field applications leave nontarget organisms at risk of exposure. We explored the effects of a common herbicide (atrazine and alachlor) and fertilizer (urea) tank mixture on juvenile frog corticosterone stress levels, acetylcholinesterase (AChE) activity, and pesticide bioaccumulation. Single agrochemical or tank mixtures were applied to terrestrial microcosms, and then individual Southern leopard frog ( Lithobates sphenocephala ) juveniles were added to microcosms for an 8‐h exposure. Afterward, frogs were transferred to aquatic microcosms for 1 h to monitor corticosterone prior to euthanasia, brain tissues were excised to evaluate AChE, and tissue homogenates were analyzed for pesticide bioconcentation with gas chromatography–mass spectrometry. Atrazine significantly increased corticosterone in frogs, particularly when combined with alachlor and urea. Atrazine increased AChE and urea decreased AChE, although no interactive effects of chemical combinations were discernible. Relative to their individual treatments, the complete tank mixture with all 3 agrochemicals resulted in 64% greater bioconcentration of atrazine and 54% greater bioconcentration of alachlor in frog tissues. Our results suggest that agrochemical mixtures as well as their active ingredients can lead to altered stress levels and impaired physiological responses in amphibians. An improved understanding of the effects of co‐exposure to environmental contaminants in amphibians is important in assessing the ecological risks these compounds pose. Environ Toxicol Chem 2019;9999:1–10. © 2019 SETAC Abstract : Acetylcholinesterase activity and corticosterone stress response in Lithobates sphenocephala after exposure to mixtures of atrazine (Z), alachlor (L), and urea (N).